A stochastic optimization approach for paper recycling reverse logistics network design under uncertainty - Kara, S. Soner; Onut, S. (SPRINGER, 2010)
One of the most important objectives of a manufacturing firm is the efficient design and operation of its supply chain to maximize profit. Paper is an example of a valuable material that can be recycled and recovered. Uncertainty is one of the characteristics of the real world. The methods that cope with uncertainty help researchers get realistic results. In this study, a two-stage stochastic programing model is proposed to determine a long term strategy including optimal facility locations and optimal flow amounts for large scale reverse supply chain network design problem under uncertainty. This network design problem includes optimal recycling and collection center locations and optimal flow amounts between the nodes in the multi-facility environment. Proposed model is suitable for recycling/manufacturing type of systems in reverse supply chain. All deterministic, stochastic models are mixed-integer programing models and are solved by commercial software GAMS 21.6/CPLEX 9.0.
Keywords: Network optimization; Recycling; Two-Stage Stochastic programming; MULTICRITERIA DECISION APPROACH; ARTIFICIAL NEURAL-NETWORK; PRODUCT RECOVERY; HAZARDOUS-WASTES; MODEL; MANAGEMENT; SYSTEM; WATER; PERFORMANCE; INDUSTRY; Environmental Sciences & Ecology